The Aussie 1918–1931: Cartoons, digger remembrance and First World War identity. (18th May 2016) - Chapman, Jane
Abstract : Feelings of community, cultural definition and memory were kept alive through the soldiers' mass circulation tabloid, the Aussie, examined here in the light of theorisation of memory and representation, applied to both text and cartoons. The publication's aim for veterans' values to become shared national values is analysed in the light of its high-profile usage of soft cartoon humour and also of nostalgia—highlighting the limitations as well as the effectiveness in terms of Australia's evolving national identity. When the post-war economic situation worsened, deeper issues of national tension were glossed over by the use of scapegoats such as "profiteers" and "lazy workers". The armed forces were obliged to take on a political role of lobbying for their cause, but the Aussie as "cheerful friend" experienced its own identity crisis that proved to be terminal.